1988
DOI: 10.1002/jnr.490190416
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of morphine to the rat somatosensory corte produces analgesia to tonic pain

Abstract: Topical application of 0.01 or 0.1% morphine solution to the somatosensory SI area of the rat cerebral cortex significantly decreased the pain intensity rating in the formalin test without producing motor side effects or sensory deficits. Naloxone partially antagonizes this effect. Topical application of morphine to the striate cortex did not induce analgesia. It is suggested that the primary somatosensory SI area of the cerebral cortex plays a role in opiate pain control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…This is supported by our observations of projections from both the insular and S2 areas of the cortex to the superficial layers of Sp5C (see also Dunn and Tolbert, 1982;Jacquin et al, 1990). Moreover, electrical stimulation of the sensorimotor cortex elicits increases in metabolic activity in several areas including the Cu and subjacent SRD (Sharp and Ryan, 1984) and application of morphine to the sensorimotor (Soto-Moyano et al, 1988) or insular (Burkey et al, 1996) cortex in the rat elicits strong antinociceptive effects. Moreover, electrical stimulation of the sensorimotor cortex elicits increases in metabolic activity in several areas including the Cu and subjacent SRD (Sharp and Ryan, 1984) and application of morphine to the sensorimotor (Soto-Moyano et al, 1988) or insular (Burkey et al, 1996) cortex in the rat elicits strong antinociceptive effects.…”
Section: Cortical Projections To the Srd And The Surrounding Cu And Ssupporting
confidence: 79%
“…This is supported by our observations of projections from both the insular and S2 areas of the cortex to the superficial layers of Sp5C (see also Dunn and Tolbert, 1982;Jacquin et al, 1990). Moreover, electrical stimulation of the sensorimotor cortex elicits increases in metabolic activity in several areas including the Cu and subjacent SRD (Sharp and Ryan, 1984) and application of morphine to the sensorimotor (Soto-Moyano et al, 1988) or insular (Burkey et al, 1996) cortex in the rat elicits strong antinociceptive effects. Moreover, electrical stimulation of the sensorimotor cortex elicits increases in metabolic activity in several areas including the Cu and subjacent SRD (Sharp and Ryan, 1984) and application of morphine to the sensorimotor (Soto-Moyano et al, 1988) or insular (Burkey et al, 1996) cortex in the rat elicits strong antinociceptive effects.…”
Section: Cortical Projections To the Srd And The Surrounding Cu And Ssupporting
confidence: 79%
“…Morphine was only effective in inhibiting behaviours when connections between the forebrain and brainstem were left intact in sham-operated rats (Matthies and Franklin 1992). Moreover, local application of morphine into either the somatosensory, prefrontal orbital or agranular insular cortices attenuates behavioural responses in the formalin pain model in rats (Soto-Moyano et al 1988; Xie et al 2004). Thus, morphine is active in the rat forebrain, which is consistent with it modulating the subjective experience of the noxious stimuli, as in humans (Jones et al 1991; Taylor et al 2013).…”
Section: What Are the Reasons For The Anthropomorphic View That Fish mentioning
confidence: 99%
“…Interestingly, it has been shown that stimulation of the sensorimotor cortex can elicit primary afferent depolarization in cutaneous nerves and Ib afferent fibers (Carpenter et al, 1962;Andersen et al, 1964), and both excitatory and inhibitory effects on sensory processing through Sp5C (Sessle et al, 1981;Jacquin et al, 1990), the dorsal column nuclei (Canedo, 1997) and the spinal dorsal horn (Fetz, 1968;Coulter et al, 1974;Yezierski et al, 1983;Zhang et al, 1991). Moreover, electrical stimulation of the sensorimotor cortex elicits increases in metabolic activity in several areas including the Cu and subjacent SRD (Sharp and Ryan, 1984) and application of morphine to the sensorimotor (Soto-Moyano et al, 1988) or insular (Burkey et al, 1996) cortex in the rat elicits strong antinociceptive effects.…”
Section: Cortical Projections To the Srd And The Surrounding Cu And Smentioning
confidence: 99%